Proposal for Slepian-States-Based DV- and CV-QKD Schemes Suitable for Implementation in Integrated Photonics Platforms - Ivan B. Djordjevic (IEEE Photonics Journal, 2019)
Quantum key distribution (QKD) leverages underlying principles of quantum mechanics to realize distribution of keys with verifiable security. Despite appealing features of QKD, there are some fundamental and technical challenges that need to be solved prior to its widespread applications. First, QKD secret-key rate (SKR) is fundamentally limited by channel loss, as dictated by the rate-loss tradeoff. Quantum repeaters would be an ultimate solution to overcome this problem; however, they are well beyond the reach. The second challenge lies in the scalability and cost. Future's QKD systems must be suitable for mass production with low cost, reliable realignment-free operations, and small power consumption. To solve for these problems in a simultaneous manner, we propose to encode information in the orthogonal Slepian sequences’ bases. Such an approach is highly robust against turbulence effects in free-space optical links and dispersion effects/fiber nonlinearities in fiber-optics channels, thereby improving QKD distance. Moreover, exploiting multidimensional encoding space enables high spectral efficiency QKD so that the SKR can be significantly improved. Critically, generation, processing, and detection of Slepian states can be reliably implemented in an integrated quantum photonics platform, based on both reflective and transmissive waveguide Bragg gratings (WBGs). Proposed reflective/transmissive WBG-based Slepian states are applicable to both discrete variable and continuous variable QKD systems.